Newborn differential DNA methylation and subcortical brain volumes as early signs of severe neurodevelopmental delay in a South African Birth Cohort Study. (14th September 2022) - Hüls, Anke; Wedderburn, Catherine J.; Groenewold, Nynke A.; Gladish, Nicole; Jones, Meaghan J.; Koen, Nastassja; MacIsaac, Julia L.; Lin, David T. S.; Ramadori, Katia E.; Epstein, Michael P.; Donald, Kirsten A.; Kobor, Michael S.; et al.
Abstract: Objectives: Early detection of neurodevelopmental delay is crucial for intervention and treatment strategies. We analysed associations between newborn DNA methylation (DNAm), neonatal magnetic resonance imaging (MRI) neuroimaging data, and neurodevelopment. Methods: Neurodevelopment was assessed in 161 children from the South African Drakenstein Child Health Study at 2 years of age using the Bayley Scales of Infant and Toddler Development III. We performed an epigenome-wide association study of neurodevelopmental delay using DNAm from cord blood. Subsequently, we analysed if associations between DNAm and neurodevelopmental delay were mediated by altered neonatal brain volumes (subset of 51 children). Results: Differential DNAm at SPTBN4 (cg26971411, Δ beta = −0.024, p -value = 3.28 × 10 −08 ), and two intergenic regions (chromosome 11: cg00490349, Δ beta = −0.036, p -value = 3.02 × 10 −08 ; chromosome 17: cg15660740, Δ beta = −0.078, p -value = 6.49 × 10 −08 ) were significantly associated with severe neurodevelopmental delay. While these associations were not mediated by neonatal brain volume, neonatal caudate volumes were independently associated with neurodevelopmental delay, particularly in language (Δ caudate volume = 165.30 mm 3, p = 0.0443) and motor (Δ caudate volume = 365.36 mm 3, p -value = 0.0082) domains. Conclusions: Differential DNAm from cord blood and increased neonatal caudate volumes were independently associated with severe neurodevelopmental delay at 2 years of age. These findings suggest that neurobiological signals for severe developmental delay may be detectable in very early life.